PENGEMBANGAN DISPOSISI DAN KONEKSI MATEMATIS SISWA MELALUI MODEL DISCOVERY LEARNING DI SEKOLAH MENENGAH KEJURUAN - Lestari, Fauji; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMathematical disposition and mathematical connections knowledge is part of mathematics learning objectives in Curriculum. Subjects in research is students of class XII AK SMK N 1 Kelam Permai. This pedagogical action research takes the subject of the study chosen purposively. The research used in this research is pedagogical action research. Two cycles with focus stage are taken into consideration in determining and planning the research, followed by look, think, and action. RPP compiled in this research is about the material sequence and arithmetic series. This RPP is prepared based on the Curriculum 2013 standard. Development of students' mathematical dispositions and connections can be done well. The initial mathematical disposition of students before using the discovery learning model is categorized as being. Early mathematical connection ability of students before using discovery learning model based on pre-test value is categorized as low. The learning process is done very well. Learning with the discovery learning model is possible to apply to schools implementing the 2013 curriculum. Learning with discovery learning model should be an alternative choice of teachers. Learning with the discovery learning model is not limited to arithmetic and sequence material only.Keywords:mathematical disposition, mathematical connections, discovery learning, mathematical knowledge.